Identification of catalase as an early up-regulated gene in Beauveria bassiana and its role in entomopathogenic fungal virulence - Chantasingh, Duriya; Kitikhun, Supattra; Keyhani, Nemat O.; Boonyapakron, Katewadee; Thoetkiattikul, Honglada; Pootanakit, Kusol; Eurwilaichitr, Lily (Biological control, 2013)
•Catalases are involved in stress tolerance and infection in entomopathogenic fungi.•CatE7 gene was identified in B. bassiana via suppression subtractive hybridization.•The catalase gene (catE7) was homologous to monofunctional fungal catalases.•A transgenic strain over-expressing BbcatE7 displayed enhanced virulence. The ability of entomopathogenic fungi to infect insects is a complex process involving differential expression of numerous genes some of which are up-regulated when the fungus is in contact with or exposed to insect cuticles. In this report, we identified a set of differentially expressed genes in the entomopathogenic fungus Beauveria bassiana BCC2659 in response to Spodoptera exigua larvae. PCR-select suppression subtractive hybridization (PCR-SSH) was used to identify genes differentially expressed during the initial aspects of the fungal-insect interaction, i.e. up to a 2h post-infection model. Ten fungal genes identified by PCR-SHH were confirmed to be up-regulated by semi-quantitative RT-PCR. Of these genes, a catalase (catE7), implicated in stress resistance, was chosen for further characterization in order to probe its role in B. bassiana pathogenesis and to determine whether over-expression would result in a more virulent strain. To investigate this, a transgenic B. bassiana strain, overexpressing CatE7 was constructed. Fungal transformant lines with extra catE7 copies (Bb::BbcatE7) showed ∼2-fold higher catalase activity than the wild type. Bb::BbcatE7 strains germinated faster than the wild-type parent and exhibited significantly higher virulence against S. exigua larvae. Although the Bb::BbcatE7 strains were no better than wild type in terms of vegetative growth in the presence of exogenous H2O2 concentrations, conidial germination rates were higher in the Bb::BbcatE7 strain in the presence of H2O2. These results suggest that responses mediated by catalases play an important role in the fungal-insect infection process and the manipulation of catalase expression can lead to more effective fungal strains for insect control.